Information asymmetry and the structure of loan syndicates - Sajid M. Chaudhry; Stefanie Kleimeier (University of Birmingham, Birmingham Business School, 2013)
This study explores the impact of information asymmetry between lenders and borrowers on loan syndicate structure. Using a sample of 17,839 loans raised by 8,701 US firms between January 1986 and August 2007, we confirm existing evidence that lead arrangers form concentrated syndicates when borrowers require intense monitoring and due diligence. We provide new evidence regarding the roles of borrower reputation, lead arranger reputation and the bank-borrower relationship. First, lead arranger reputation can reduce information asymmetry but only for the most reputable lead arrangers. Second, borrower reputation, measured by the borrower's past access of the loan market, reduces the problem of information asymmetry, with higher reductions for more recent and more regular borrowers. Third, our results regarding the past relationship between the borrower and the lead arranger support the moral hazard aspect of information asymmetry for all borrowers. We also find evidence for the adverse selection aspect of information asymmetry but only for opaque borrowers. The effect can, however, be overcome by the most reputable lead arrangers, as their behavior is strongly influenced by a fear of loss of reputation.
Keywords: D82; G21; 330; syndicated loans; syndicate structure; information asymmetry; reputation